2005
DOI: 10.1074/jbc.m412774200
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Human Metaphase Chromosomes

Abstract: DNA is packaged as chromatin in the interphase nucleus. During mitosis, chromatin fibers are highly condensed to form metaphase chromosomes, which ensure equal segregation of replicated chromosomal DNA into the daughter cells. Despite >1 century of research on metaphase chromosomes, information regarding the higher order structure of metaphase chromosomes is limited, and it is still not clear which proteins are involved in further folding of the chromatin fiber into metaphase chromosomes. To obtain a global vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
142
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(154 citation statements)
references
References 66 publications
(71 reference statements)
11
142
0
Order By: Relevance
“…In our recent proteome analysis, 107 proteins were identified in highly purified human metaphase chromosomes (Uchiyama et al, 2005). Furthermore, the observation that more than a quarter of the identified proteins were classified as chromosome peripheral proteins strongly suggests that these proteins are related to either chromosome organization or mitotic progression.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent proteome analysis, 107 proteins were identified in highly purified human metaphase chromosomes (Uchiyama et al, 2005). Furthermore, the observation that more than a quarter of the identified proteins were classified as chromosome peripheral proteins strongly suggests that these proteins are related to either chromosome organization or mitotic progression.…”
Section: Introductionmentioning
confidence: 99%
“…Two small proteins that are likely to be important to chromatin folding are high-mobility-group (HMG) proteins, and the barrier-to-integration-factor (BAF-1) protein (Margalit et al 2007), which are present in mitotic chromosomes in numbers comparable to those of histones (Uchiyama et al 2005). HMG proteins are divided into three families with different functions (Hock et al 2007): HMGA proteins bind AT-rich DNA, HMGB proteins bend DNA (Thomas & Travers 2001), and HMGN proteins reorganize nucleosomes.…”
Section: Chromatin Fibrementioning
confidence: 99%
“…Proteomic analyses under different conditions indicated that CPPs remain to be associated even with highly purified chromosomes. In contrast, most chromosomal coating proteins, including mitochondrial or endoplasmic reticulum (ER) proteins, are lost from chromosomes under the same conditions (17,18). This suggests that the chromosome periphery is maintained as a chromosomal structure, resisting isolation and purification procedures or mechanical treatments.…”
Section: What Is the Chromosome Periphery?mentioning
confidence: 92%
“…Immunostaining with antibodies against several CPPs and localization analyses of GFP-fused CPPs also demonstrated that the chromosome periphery is not an experimental artifact but a chromosome structure (7,17). Recent proteome analyses of metaphase chromosomes revealed that human chromosomes consist of four layers, including the chromosome periphery (17). Proteomic analyses under different conditions indicated that CPPs remain to be associated even with highly purified chromosomes.…”
Section: What Is the Chromosome Periphery?mentioning
confidence: 99%
See 1 more Smart Citation